O‘ZBEKISTONDA HELOBDELLA BLANCHARD, 1896 URUG‘IGA MANSUB ZULUKLARNING MOLEKUYLAR IDENTIFIKATSIYASI - Kuchboyev , A.E; Solijonov , X.X; Izzatullayev , Zuvayd; Umarov F.U, Umarov F.U; Usmonov S.X., Usmonov S.X.; Izatullayev X.I., Izatullayev X.I. (Actual problems and prospects of the study of the fauna, 2024)
GeneJET Genomic DNA Purification Kit (Thermo Fisher Sciences, USA) was used to isolate DNA from species of Helobdella sp. to obtain pure and high-yield DNA, and the amount of DNA in it is sufficient for PCR amplification. Helobdella leech specimens collected from Ferghana and Surkhandarya regions were examined using mtDNA COI gene primers and compared with the species in the international Genbank (NCBI) database, it was found that the related species are Helobdella europaea Kutschera, 1987 and Helobdella stagnalis (Linnaeus 1758).